Assessment of ERP Implementation Readiness in SKPD Indramayu Regency Using People Process Technology (PPT) Model and PLS-SEM Method - Anindita, Ramya (Green Publisher Indonesia, 2025)
The implementation of e-Government in Indonesia is crucial for enhancing public service quality and efficiency, yet local governments face significant challenges. This research analyzes the readiness for Enterprise Resource Planning (ERP) implementation in Regional Apparatus Work Units (SKPD) of Indramayu Regency, utilizing the People Process Technology (PPT) model and Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. The study aims to assess the influence of human resources, processes, and technology on ERP readiness. Data were collected through questionnaires and interviews with five SKPD agencies, focusing on the critical dimensions of readiness. The findings reveal that the people variable significantly affects ERP implementation readiness, while process and technology variables show very weak effects. This suggests that optimizing human resources is essential for successful ERP adoption. Recommendations include enhancing training programs, improving business process alignment, and focusing on technological readiness through targeted skill development and security audits. The implications of this research provide valuable insights for local governments in planning and managing ERP implementations more effectively, addressing existing constraints, and enhancing organizational readiness. By focusing on these areas, local governments can better support the successful adoption of e-Government initiatives, ultimately improving service delivery and operational efficiency in the public sector.